Pembelajaran Pendidikan Karakter Di Sekolah Minggu Gereja Toraja (SMGT) Jemaat Rantepangli - Lesta Mega Lesta; Johar Linda; Asia Ramli (Penerbit dan Percetakan, CV. Picmotiv, 2025)
This study aims to describe the character education values contained in the lyrics of Sunday School songs at the Toraja Church Sunday School (SMGT) of the Rantepangli Congregation and describe the implementation of Sunday School songs to improve character education at the Toraja Church Sunday School (SMGT) of the Rantepangli Congregation. The type of research used in this study is descriptive and document analysis method. Descriptive method can be interpreted as a method used to describe or analyze a research result but is not used to make broader conclusions. The analysis method used is descriptive analysis, because it aims to describe the image and form of the song with the meaning and values contained in the song. Data collection techniques include observation, interviews, and documentation. From this study, data was obtained that there are several songs used in the Sunday School inadah that contain character education values. such as; (1) The song “S’gala Puji Syukur”. (2) The song “Aku Anak Terang”. (3) The song “ Mari Kerja Sama-sama”. (4) The song “Aku Senang Jadi Anak Tuhan”. (5) The song “Lima Jari Kananku”. (6) The song “Indonesia Negaraku”. (7) The song “Baca Kitab Suci”. (8) The song Ku Kasihi Kau dengan Kasih Tuhan”. (9) The song “Kasihi Musuhmu”. Sunday School songs are taught to children during regular Sunday worship services. Teachers serve as role models in teaching the songs. In this process, Sunday School teachers utilize technology such as LCD monitors and loudspeakers to facilitate children's understanding of the songs. The repetitive use of songs can help children understand the values contained within the songs, particularly the character education values that are beneficial for child development.